Hydrogen bond guidance and aromatic stacking drive liquid-liquid phase separation of intrinsically disordered histidine-rich peptides - Bartosz Gabryelczyk (Nature Portfolio, 2019)
Liquid-liquid phase separation (LLPS) of intrinsically disordered proteins plays an important part in the formation of extracellular biological materials. Here, the authors show that repeats of the peptide motif GHGLY are necessary for the LLPS of pH-responsive histidine-rich squid beak proteins.